Modern Geodata Management: Application of Interdisciplinary Interpretation and Visualization in Central America. (2nd June 2009) - Damm, T.; Götze, H.-J.
Abstract : In the last years new methods of data acquisition and processing in geosciences, inspired by growing computer performance, have led to an increased amount of data, and this development will proceed surely. In this paper we present the conception and technical realization of an interdisciplinary research group's geodata management as a combination of a metadata catalog together with web mapping technology. Clearly related with the storage and retrieval of different datasets is the need of visualization. 3D visualization in geoscientific interpretation is a useful tool, if numerous, heterogenic datasets have to be visualized at the same time. Moreover, advanced sensing technology often generates native three-dimensional datasets. Using a case study from the Collaborative Research Centre "SFB 574", we present the possibilities of our stereoscopic projection system and want to explain the benefit of 3D visualization for research in general and university education in particular, as low-cost systems become available nowadays.